Isometric Exercise of Quadriceps and Gluteal Muscle in Patient with Close Femur Fracture - Sri Wirayuni; Liya Arista (JIKO (Jurnal Ilmiah Keperawatan Orthopedi), 2021)
Femur fracture is a fracture in the largest bone in the body. The femur requires significant force to fracture. One of the treatments for femoral fracture is reduction and immobilization using traction. Immobilization in traction-attached patients before preoperatively requires isometric exercises to maintain muscle strength. Isometric exercise is a muscle contraction exercise, the patient contracts the muscles without moving the muscles to maintain muscle and prevent atrophy. The purpose of this paper is to identify the effectiveness of isometric exercises to increase isometric muscle strength in patients with lower limb fracture. The methodology used is a case study. The application of isometric exercises can increase muscle strength in patients with skin traction attached. Nurses need to pay attention to factors that can affect the patient's ability to perform isometric exercises so that the results obtained can be more optimal and the patient experiences an increase in the ability of his limbs.